An ~1,100-year record of human and seabird occupation in the High Arctic inferred from pond sediments ... - Cheng, Wenhan; Kimpe, Linda; Mallory, Mark; Smol, John; Blais, Jules (My University, 2021)
Seabirds in the Canadian Arctic congregate in large colonies producing oases of biological productivity and diversity in coastal regions. Here we examine sterols, stanols, and stable isotopes (15N, and 13C) in three 14C-dated pond sediment cores near a large seabird colony and archeological site on Devon Island, showing historical occupation by the seabirds and an ancient human (Thule or Norse) settlement over ~1,100 years. Coprostanol in the sediment records captures the presence of humans at ca. 1150 CE, followed by their abandonment of the site by ca. 1300 CE. Seabird presence at this site after ca.1200 CE is indicated by increases in δ15N and cholesterol/sitosterol. Seabird population expansion is observed after ca. 1600 CE in δ15N and cholesterol/sitosterol profiles, coinciding with European whaling activities that expanded in the 17th-19th centuries. Our study provides insights to human and seabird occupation in the High Arctic to inform archeological and conservation efforts. ...